GT4CCI: uma abordagem baseada em grounded theory para a identificação de interesses transversais em documentos de requisitos - Sobral, Larissa de Alencar (2013)
When crosscutting concerns identification is performed from the beginning of development, on the activities involved in requirements engineering, there are many gains in terms of quality, cost and efficiency throughout the lifecycle of software development. This early identification supports the evolution of requirements, detects possible flaws in the requirements specification, improves traceability among requirements, provides better software modularity and prevents possible rework. However, despite these several advantages, the crosscutting concerns identification over requirements engineering faces several difficulties such as the lack of systematization and tools that support it. Furthermore, it is difficult to justify why some concerns are identified as crosscutting or not, since this identification is, most often, made without any methodology that systematizes and bases it. In this context, this paper proposes an approach based on Grounded Theory, called GT4CCI, for systematizing and basing the process of identifying crosscutting concerns in the initial stages of the software development process in the requirements document. Grounded Theory is a renowned methodology for qualitative analysis of data. Through the use of GT4CCI it is possible to better understand, track and document concerns, adding gains in terms of quality, reliability and modularity of the entire lifecycle of software